Relationship between the ablation index, lesion formation, and incidence of steam pops. Issue 4 (1st June 2019) - Mori, Hitoshi; Kato, Ritsushi; Sumitomo, Naokata; Ikeda, Yoshifumi; Goto, Koji; Tanaka, Sayaka; Asano, So; Tahara, Mai; Nagase, Takahiko; Iwanaga, Shiro; Muramatsu, Toshihiro; Matsumoto, Kazuo
Abstract: Background: The ablation index (AI) is reported to be useful for a durable pulmonary vein isolation (PVI). However, there have been no studies investigating the relationship between the power, contact force (CF), AI, and steam pops. Methods: Using an in vitro model, ablation energy was delivered until a steam pop occurred and the time to the steam pop and AI when the steam pop occurred were measured. The experiment was performed with a combination of various powers (20, 30, 40, and 50 W) and contact forces (CFs) (10, 30, and 50 g) 20 times for each setting. The analysis consisted of two protocols. The first protocol was a comparison between the ablation power and several parameters under the same CF (10, 30, and 50 g). The second protocol was a comparison between the CF and several parameters under the same power (20, 30, 40, and 50 W). The correlation between the lesion formation and ablation parameters was evaluated. Results: The AI value when steam pops occurred varied depending on the ablation settings. All AI median values were <500 under an ablation power of 50 W. On other hand, the median ablation time up to the steam pop was more than 46 seconds, but all median values of the AI were more than 550 under an ablation with 20 W. Conclusions: The AI cannot predict steam pops. A low power and long duration ablation could obtain a high AI value. However, high‐power ablation could not obtain a high AI value because of an early occurrence of steam pops.